2008
DOI: 10.1016/j.jacc.2008.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Turbulence: Standards of Measurement, Physiological Interpretation, and Clinical Use

Abstract: This consensus statement has been compiled on behalf of the International Society for Holter and Noninvasive Electrophysiology. It reviews the topic of heart rate turbulence (HRT) and concentrates on technologies for measurement, physiologic background and interpretation, and clinical use of HRT. It also lists suggestions for future research. The phenomenon of HRT refers to sinus rhythm cycle-length perturbations after isolated premature ventricular complexes. The physiologic pattern of HRT consists of brief h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
440
1
39

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 397 publications
(490 citation statements)
references
References 114 publications
10
440
1
39
Order By: Relevance
“…This is in contrast to their independent predictive power in post-MI patients (10,14,20). In this study, we observed modest (r=0.2-0.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This is in contrast to their independent predictive power in post-MI patients (10,14,20). In this study, we observed modest (r=0.2-0.…”
Section: Discussioncontrasting
confidence: 82%
“…HRT estimates cardiac baroreceptor reflex function from the responses of NN intervals to putative transient arterial pressure reduction caused by ventricular premature contraction (VPC). The patterns of responses are classified into the following categories: normal (category 0), partially abnormal (category 1), and abnormal (category 2) (9,12,20). This measure is available only when .5 isolated VPCs suitable for the analysis are obtained from 24-hour electrocardiography.…”
Section: Hrv Analysesmentioning
confidence: 99%
“…Для ТРС определяли показатели turbulence onset (ТО) (начало турбулентности -величина учащения сину-сового ритма после ЖЭ) и turbulence slopе (TS) (наклон турбулентности -интенсивность замедления синусового ритма после его учащения в постэкстрасистолическом пе-риоде). За патологические значения принимали ТО ≥0%, TS ≤2,5 мс/RR [7]. При отсутствии ЖЭ, пригодных для анализа за время ХМ, ТРС считали нормальной [7,8].…”
Section: материал и методыunclassified
“…За патологические значения принимали ТО ≥0%, TS ≤2,5 мс/RR [7]. При отсутствии ЖЭ, пригодных для анализа за время ХМ, ТРС считали нормальной [7,8].…”
Section: материал и методыunclassified
See 1 more Smart Citation